2015
DOI: 10.1007/s11523-015-0387-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuing First-Line EGFR Tyrosine Kinase Inhibitor Therapy Beyond RECIST Disease Progression in Patients with Advanced EGFR-Mutated Non-Small-Cell Lung Cancer (NSCLC): Retrospective GFPC 04-13 Study

Abstract: NCT02293733.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Median OS was similar for patients who received EGFR TKIs as post-PD therapy ( n  = 36), which were mainly continuous erlotinib administration following RECIST PD ( n  = 21) (Table 3), and for those who did not. In contrast to our findings, in a retrospective study of patients with activating EGFR mutations ( n  = 123) who were treated with EGFR TKIs, OS showed a trend in favor of continuing versus discontinuing EGFR TKI treatment following RECIST PD (33.0 versus 21.2 months, respectively; p  = 0.054) [25]. Furthermore, a retrospective clinical modeling study that evaluated the usefulness of EGFR TKI failure pattern for selecting subsequent management, suggested that the efficacy of EGFR TKI continuation differed between patients with gradual progression, local progression, and dramatic progression [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Median OS was similar for patients who received EGFR TKIs as post-PD therapy ( n  = 36), which were mainly continuous erlotinib administration following RECIST PD ( n  = 21) (Table 3), and for those who did not. In contrast to our findings, in a retrospective study of patients with activating EGFR mutations ( n  = 123) who were treated with EGFR TKIs, OS showed a trend in favor of continuing versus discontinuing EGFR TKI treatment following RECIST PD (33.0 versus 21.2 months, respectively; p  = 0.054) [25]. Furthermore, a retrospective clinical modeling study that evaluated the usefulness of EGFR TKI failure pattern for selecting subsequent management, suggested that the efficacy of EGFR TKI continuation differed between patients with gradual progression, local progression, and dramatic progression [26].…”
Section: Discussioncontrasting
confidence: 99%
“…The IMPRESS study demonstrated no benefit of continued 1st EGFR-TKI with chemotherapy after RECIST progression in comparison to chemotherapy alone24. However, in patients with isolated disease progression after development of resistance to 1st EGFR-TKI, continuation of 1st EGFR-TKI in combination with local therapy is feasible, and subsequent treatment can be postponed252627. In our present study, patients with EGFR exon 19 deletion mutation who received long-term treatment with 1st or 2nd EGFR-TKI demonstrated a high prevalence of T790M mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In IMPRESS trial, continuation of gefitinib treatment after disease progression on gefitinib monotherapy did not prolong progression-free survival and overall survival in patients who received platinum-based doublet chemotherapy as subsequent line of treatment [26]. However, it is unclear that the efficacy of continuous using EGFR-TKIs without platinum doublets [27, 28]. Recently, we had been able to use third generation EGFR-TKIs that have great efficacy for NSCLC with EGFR T790M mutation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%